Lettere 1935-1972 Con una raccolta di racconti dispersi - Dessì, Giuseppe (Moderna/Comparata, 2015)
Just over 150 epistolary pieces, from the twentieth-century archives of Florence and Rome, are published for the first time thanks to Alberto Baldi's careful transcription, which does not only allow the reconstruction of the story of a friendship born around the pages of newspapers and consolidated over time to involve the partners of the two writers (Gianna Manzini, Lina Baraldi and Luisa Babini), but also follows Giuseppe Dessí's presence in one of the most widely read newspapers in Rome. The editorial correspondence, started early by Falqui, the "mover of culture" and through frequency peaks (from 1948 to 1958), soon turned into the advice of a sympathetic reader who, despite the political dissensions for the conservative line of the newspaper "Il Tempo", deserves the credit of having continued a collaboration which would nourish some of the writer's most significant collections of short stories. The book ends with thirty-eight narrative texts by Dessí, scattered on the «third page» and never collected in a volume before.